Power linear proton and heavy ion accelerators for solving scientific and practical problems - Bomko, V.A. (Вопросы атомной науки и техники, 2005)
A scope of the important problems which solving requires the availability of powerful proton and heavy ions beams is presented. The most important among them are creation of effective and safe nuclear energetics with inexhaustible fuel resources based on a complex of a proton linear accelerator and a subcritical reactor on fast neutrons; creation of intensity neutron generators for investigation of the structure and dynamics of condensed matter; the use of intense proton beams of high energy for creation of µ-meson and neutrino factories for application in physics of weak interactions. Information about investigations on radionuclide and heavy ion beams accelerated for high energy is presented. Представлено огляд актуальних проблем, вирішення яких вимагає потужних прискорювачів протонів і важких іонів. Серед них найбільш важливими є створення ефективної і безпечної ядерної енергетики з невичерними ресурсами палива на базі комплексу лінійного прискорювача протонів і підкритичного реактора на швидких нейтронах; створення інтенсивних нейтронних генераторів для вивчення структури і динаміки конденсованої матерії; використання інтенсивних пучків протонів для створення фабрик μ-мезонів та нейтрино для фізики слабких взаємодій. Представлено огляд матеріалів, що відносяться до досліджень на пучках радіонуклідів та важких іонів, прискорених до високих енергій. Представлен обзор актуальных проблем, решение которых требует мощных ускорителей протонов и тяжелых ионов. Среди них наиболее важными являются создание эффективной и безопасной ядерной энергетики с неисчерпаемыми ресурсами топлива на базе комплекса линейного ускорителя протонов и подкритического реактора на быстрых нейтронах; создание интенсивных нейтронных генераторов для изучения структуры и динамики конденсированной материи; использование интенсивных пучков протонов для создания фабрик μ-мезонов и нейтрино для физики слабых взаимодействий. Представлен обзор материалов по исследованиям на пучках радионуклидов и тяжелых ионов, ускореных до высоких энергий.